Mechanisms of Keap1/Nrf2 modulation in bacterial infections: implications in persistence and clearance - Romero-Durán, Marco Antonio; Silva-García, Octavio; Perez-Aguilar, Jose Manuel; Baizabal-Aguirre, Víctor Manuel (Frontiers in Immunology, 2024)
Pathogenic bacteria trigger complex molecular interactions in hosts that are characterized mainly by an increase in reactive oxygen species (ROS) as well as an inflammation-associated response. To counteract oxidative damage, cells respond through protective mechanisms to promote resistance and avoid tissue damage and infection; among these cellular mechanisms the activation or inhibition of the nuclear factor E2-related factor 2 (Nrf2) is frequently observed. The transcription factor Nrf2 is considered the master regulator of several hundred cytoprotective and antioxidant genes. Under normal conditions, the Keap1/Nrf2 signaling protects the cellular environment by sensing deleterious oxygen radicals and inducing the expression of genes coding for proteins intended to neutralize the harmful effects of ROS. However, bacteria have developed strategies to harness Nrf2 activity to their own benefit, complicating the host response. This review is aimed to present the most recent information and probable mechanisms employed by a variety of bacteria to modulate the Keap1/Nrf2 activity in order to survive in the infected tissue. Particularly, those utilized by the Gram-positive bacteria Staphylococcus aureus, Streptococcus pneumoniae, Listeria monocytogenes, and Mycobacterium tuberculosis as well as by the Gram-negative bacteria Escherichia coli, Helicobacter pylori, Legionella pneumophila, Pseudomonas aeruginosa and Salmonella typhimurium. We also discuss and highlight the beneficial impact of the Keap1/Nrf2 antioxidant and anti-inflammatory role in bacterial clearance.